NURS-05. MULTI-INSTITUTIONAL NEURO-ONCOLOGY NURSING COLLABORATION: THE PEDIATRIC BRAIN TUMOR CONSORTIUM NURSING COMMITTEE EXPERIENCE - Hancock, Lauren (Neuro Oncol, 2018)
INTRODUCTION: The Pediatric Brain Tumor Consortium (PBTC) was founded in 1999 by the National Cancer Institute (NCI) to improve the treatment of primary brain tumors in children. Nurses have long played an integral role in the care of children enrolled on PBTC clinical trials; however a nursing committee was not formalized until 2013. METHODS: With the support of the PBTC scientific committee and after review of the literature regarding supportive care in pediatric brain tumor patients, a nursing committee was conceptualized to begin with yearly meetings. We describe the experience of the PBTC nursing committee and the challenges and rewards of multi-institutional nursing collaboration. RESULTS: The creation of this nursing committee in 2013 led to more active nursing participation, having a nurse assigned to each clinical trial, and led to the development of a nursing-led quality of life protocol. CONCLUSION: The nursing care of children with brain tumors can present unique challenges. Collaboration with nurses at multiple institutions can provide innovative new approaches to supportive care, leading to improved quality of life for patients with brain tumors.